A multicenter phase II prospective clinical trial of glucocorticoid for patients with untreated IgG4-related disease. Issue 5 (3rd September 2017) - Masaki, Yasufumi; Matsui, Shoko; Saeki, Takako; Tsuboi, Hiroto; Hirata, Shintaro; Izumi, Yasumori; Miyashita, Taiichiro; Fujikawa, Keita; Dobashi, Hiroaki; Susaki, Kentaro; Morimoto, Hisanori; Takagi, Kazutaka; et al.
Abstract: Objective: Although glucocorticoids are effective for patients with IgG4-related disease, the treatment has not yet been standardized. Therefore, the treatment strategy should be established. Patients and methods: Patients who fulfilled the comprehensive diagnostic criteria for definite IgG4-related disease were started on prednisolone (0.6 mg/kg body weight) with the dose reduced every two weeks. The subsequent maintenance dose and need for prednisolone were determined for individual patients. The primary endpoint was the complete remission (CR) rate at one year. Secondary endpoints included overall response rate (ORR), the maintenance dose, the relapse rate, and adverse events. Results: This study enrolled 61 patients. After clinicopathological review, three patients were excluded, and one, 13, and 44 patients were diagnosed with probable, possible, and definite IgG4-related disease, respectively. Of the 44 patients with definite IgG4-RD, 29 (65.9%) achieved CR, and the ORR was 93.2%. No patient was refractory to primary treatment. The most frequent adverse events were glucose intolerance. Six patients relapsed. Conclusions: Glucocorticoid treatment is usually effective for patients with IgG4-RD, and we should examine the possibility of other disorders when a patient is glucocorticoid refractory. Some patients are misdiagnosed, making central clinicopathological review of diagnosis very important in conducting clinical studies.